Broadening perceptions of economics in a new introductory economics sequence. Issue 3 (4th May 2021) - Owen, Ann L.; Hagstrom, Paul
Abstract: The article's authors report on a comprehensive curricular reform aimed at communicating the broad range of social issues that economists study while engaging students in active learning strategies. The reform increased interest in taking additional economics courses and majoring in economics, broadened students' views of what economists do, and imparted more content to students. Female students earn higher grades under the revised curriculum, but no differential impact on interest in majoring in economics for female students, students of color, or first generation college students is found. Engaging students with empirical work on important social issues appeals to all students, resulting in more majors from both under- and overrepresented groups, but generates little impact on the percentage of students majoring in economics from underrepresented groups.